Spatial Distribution of Ray Craters on Callisto: Implications for Ray Retention and Impactor Sources on Jovian Satellites. Issue 7 (2nd July 2019) - Xu, Luyuan; Hirata, Naoyuki; Miyamoto, Hideaki
Abstract: Ray craters are good indicators for deciphering the most recent cratering rate and surface alteration rate on a solar system solid body. We utilize Voyager and Galileo images to examine the distribution of ray craters ( D > 10 km) on Callisto. We identify a total of 57 ray craters and 279 rim deposit craters and find that ray craters ( D > 25 km) on Callisto show a pronounced decreasing apex‐antapex asymmetry (i.e., crater density decreases from the center of the leading hemisphere to the center of the trailing hemisphere), which would be consistent with a heliocentric origin, but the degree of the asymmetry is much lower than the theoretical expectation for ecliptic comets. A possible explanation for this is the preferential surface alteration rate on the leading hemisphere. The retention times of ray craters on Callisto are slightly longer than those on the dark terrain of Ganymede; this is possibly because of the substantially weaker micrometeorite gardening or/and sputtering on Callisto than those on Ganymede. The slope of the size‐frequency distribution of ray craters on Callisto is shallower than that of all impact craters, which is due to the higher erasure rate for the smaller craters' rays. Plain Language Summary: Distributions of impact craters can give insights into the sources of impactors and geological processes on a planetary body. However, the records of all impact craters on Callisto might have lost crucial information due to crater saturation. Instead, ray craters could serve as better indicators because they are much younger and unsaturated. This study examines the distributions of ray craters on Callisto and conducts comparisons of the ray crater distributions on Callisto and Ganymede. We find that large ray craters on Callisto exhibit a pronounced decreasing apex‐antapex asymmetry similar to those on the bright terrain of Ganymede, which is inconsistent with the previous view that Jovian impactors are mainly from ecliptic comets. Multiple explanations may be responsible for these trends, one being that differential surface alteration rate may preferentially erase rays on the leading hemisphere. Key Points: The distributions of ray craters on Callisto by using both Voyager and Galileo images are examined Large ray craters on Callisto exhibit a pronounced apex‐antapex asymmetry, similar to those on the bright terrain of Ganymede Differential surface alteration rate may preferentially erase rays on the leading hemisphere